2022
DOI: 10.3390/biomedicines10092095
|View full text |Cite
|
Sign up to set email alerts
|

Real-Life Performance of F-18-FDG PET/CT in Patients with Cervical Lymph Node Metastasis of Unknown Primary Tumor

Abstract: Background: Neoplasms in the head and neck region possess higher glycolytic activity than normal tissue, showing increased glucose metabolism. F-18-Flourodeoxyglucose (FDG) positron emission tomography/computed tomography (PET/CT) can identify an unknown primary tumor (CUP). Aim: The aim of this study was to assess the real-life performance of F-18-FDG-PET/CT in detecting primary sites in patients with cervical lymph node metastasis of CUP. Methods: A retrospective data analysis of 31 patients who received FDG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
1
1
0
Order By: Relevance
“…All of our patients were histopathologically confirmed with CUP, but in these studies, only some of the patients were histopathologically indicated, which have resulted in the relatively low rates of primary tumor detection on PET/CT. Most patients had tumors in the head and neck and lung, which is consistent with other reports in the literature; 28 , 29 nonetheless, the histopathologic results showed that adenocarcinoma was the most frequent tumor, followed by squamous cell carcinoma. This result may be attributed to the following reason: head and neck tumors include nasopharyngeal cancer, oropharyngeal cancer, laryngeal cancer, and hypopharyngeal cancer, which can contribute to the highest incidence of head and neck cancer in statistics.…”
Section: Discussionsupporting
confidence: 89%
“…All of our patients were histopathologically confirmed with CUP, but in these studies, only some of the patients were histopathologically indicated, which have resulted in the relatively low rates of primary tumor detection on PET/CT. Most patients had tumors in the head and neck and lung, which is consistent with other reports in the literature; 28 , 29 nonetheless, the histopathologic results showed that adenocarcinoma was the most frequent tumor, followed by squamous cell carcinoma. This result may be attributed to the following reason: head and neck tumors include nasopharyngeal cancer, oropharyngeal cancer, laryngeal cancer, and hypopharyngeal cancer, which can contribute to the highest incidence of head and neck cancer in statistics.…”
Section: Discussionsupporting
confidence: 89%
“…For diagnosing CC, five eligible studies utilizing FDG PET/CT and FDG PET/MRI with a total of 188 patients were included [114][115][116][117][118]. The sensitivity and specificity of FDG PET/CT in CC diagnosis ranged from 75% to 86.66% and 44.4% to 96%, respectively [115,118].…”
Section: Staging or Diagnosis Of Primary CCmentioning
confidence: 99%